Performance Analysis of Hybrid Electric Vehicle Architectures Under Dynamic Operating Conditions - B. Raja Siddharth, V. Sai Chandu, D. Mani Babu,D. John Pradeep,Y. V. Pavan Kumar (International Journal of Advanced Science and Technology, 2020)
Mobility is important in any emerging economies and vehicles to play a key role in transportation. Increased use of vehicles that run on fossil fuels accelerates global warming process and increase particulate pollution which is harmful to nature. Electric vehicle technology (EVT) aims at the reduction of pollutants released into the environment and provides a reliable alternative to fossil fuels, which is on a depleting trend all over the globe. However, the EVT suffers from high initial investment costs and sophisticated charging methods, based on which Hybrid electric vehicle technology (HEVT) is probed. HEVT use an electric motor as well as an internal combustion engine, which use battery power and fossil fuels respectively for vehicle mobility. It has the capability to shift the vehicle power from fuel to battery, battery to fuel or both simultaneously depending upon the user requirement, terrain conditions, etc. The HEVT can be realized by four architectures, namely P1, P2, P3 and P4. The performance of all these architectures under various dynamic operational conditions is analyzed in this paper. The efficacy of these architectures is tested for parameters such as the speed of the vehicle, battery charge profile, IC engine/electric motor power profiles, and fuel consumption under dynamic operating conditions such as continuous acceleration, pulse acceleration, and step-up acceleration. The modelling/simulation is done in Simulink. From the comparative results, the recommendations have been derived based on performance needs.